2011
DOI: 10.1177/097324701100700207
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of TQM: A Case Study in an Auto Company

Abstract: This case study has been carried on Total Quality Management (TQM) implementation in an auto company. The XYZ auto company is producing auto parts and components to large scale auto companies producing the various automotive vehicles. XYZ Auto Company is the best and tier one supplier to about 3 companies and their branches located in different places. This XYZ auto company is already an ISO 9000 certified company and planning to implement the TQM philosophy and best practicing the TQM tools and techniques in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…These findings were in line with the findings of Martin & Barth (2018) who established that performances of tea factories is about lean production through elimination of unnecessary modes of transport, over stocking, ensuring equipment utilization, reduction in production delays, reduction of excessive production that leads to excess waste and ensure maximum utilization of labor. The findings to a large extent corroborate with the findings of Venkateshwarlu, Ashish and Manoj, (2011) which found out that firms can improve their performances with adoption of lean procurement practices. Tea factories in Kericho should therefore adopt lean practices in order to improve their performances.…”
Section: Page: 1306supporting
confidence: 87%
See 1 more Smart Citation
“…These findings were in line with the findings of Martin & Barth (2018) who established that performances of tea factories is about lean production through elimination of unnecessary modes of transport, over stocking, ensuring equipment utilization, reduction in production delays, reduction of excessive production that leads to excess waste and ensure maximum utilization of labor. The findings to a large extent corroborate with the findings of Venkateshwarlu, Ashish and Manoj, (2011) which found out that firms can improve their performances with adoption of lean procurement practices. Tea factories in Kericho should therefore adopt lean practices in order to improve their performances.…”
Section: Page: 1306supporting
confidence: 87%
“…Quality tea production through implementation of lean manufacturing practices like total quality management has enabled tea factories in India become excellent competitors (Venkateshwarlu, Ashish & Manoj, 2011). Adoption of lean and six sigma practices enables firms to reduce waste and defects respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The in-depth review of studies indicated that the TQM concept has been successfully implemented both in large (Flynn et al , 1995; Ahire et al , 1996) and small and medium enterprises (SMEs) (Azam et al , 2023; Ali et al , 2022). In terms of manufacturing type, most studies focus on electrical and electronic (E&E) firms and automotive (Ahire et al , 1996; Abdi and Singh, 2022; Venkateshwarlu et al , 2011) but less focus on pharmaceutical (Albuhisi and Abdallah, 2018; Tipton, 2011), food and beverages (Psomas et al , 2014).…”
Section: Theory Context Characteristics and Methodology Frameworkmentioning
confidence: 99%